Efectivitiy of Guidelines for Basic Motion Techniques for Volleyball Games with Biomechanics Analysis KINOVEA Application Based on Video Volleyball Games - Labib Labib; Muhammad Muhyi; Harwanto Harwanto (IKIP Budi Utomo Malang, 2021)
This study aims to determine the validity and effectiveness of the basic movement technique guidelines for volleyball games with biomechanical analysis using the kinovea application. The results of this study are expected to improve students' ability to understand and master basic volleyball techniques effective and efficient. Development research is used to answer the problems found. The research was conducted on SMK/SMA level students from January to April 2021. The research instruments include the kinovea application, interview guide, documentation, and the effectiveness test questionnaire sheet from the manual that will be filled out by the respondent. The results showed that the development of a basic technique manual for playing volleyball was effective. As evidence of the feasibility of the book, 80.1% of the small group test is feasible, the medium group test is 88.1% very feasible category, and the large group test shows that 89.1% is in the very feasible category. Based on the test results of small, medium, and large groups, the development of a basic technical manual for playing volleyball for SMK Negeri 1 Surabaya is quite practical. As a further suggestion, it is necessary to develop types of games that support the introduction of basic techniques in volleyball.